Calculated tunneling magnetoresistance ratio of FeRh/MgO/FeRh (001) magnetic tunnel junction. (October 2018) - Sakhraoui, T.; Said, M.; Alouani, M.
Abstract: The electronic transport properties across the FeRh/MgO/FeRh (001) magnetic tunnel junction have been investigated under an external voltage bias employing the density functional theory in conduction with the non-equilibrium Green's formalism as implemented in TranSIESTA. The results show that by increasing the external voltage bias the current increases nonlinearly. It's claimed that the variation of the electronic coupling between the oxide and the electrodes with the external bias leads to this behavior. The large difference of the k || -resolved transmission at the Fermi level between the parallel (P) and antiparallel (AP) magnetizations of the electrodes can be explained by the k || -resolved density of states. It is also shown that the transmission is not dominated by the contribution at the "Γ" point like in Fe/MgO/Fe MTJ. This large difference between the P and AP transmissions led to a huge tunneling magnetoresistance ratio at zero bias. Highlights: Theoretical study of the spin-dependent transport properties of FeRh/MgO/FeRh (001) MTJ. Nonlinear I-V curve and IRS modified by the magnetization orientation and voltage bias. Tunnel currents are calculated for both majority- and minority-spins under P and AP alignments of the two FeRh electrodes. Huge calculated TMR.